Aline MacMahon : Hollywood, the Blacklist, and the Birth of Method Acting - Stangeland, John (Book collections on Project MUSE., 2022)
American actress Aline MacMahon's youth was spent honing her talents while performing at local events in New York City. After popular stage success on Broadway, she headlined a touring company in Los Angeles, where she was discovered by legendary Hollywood director Mervyn LeRoy and put under contract to Warner Brothers. During the 1930s and 1940s, MacMahon starred in countless films and was among the most influential actors of the era, her talent revered as highly as peers Katherine Hepburn, Paul Muni, and Bette Davis. Her pioneering use of a new acting style brought to America from Russia by Konstantin Stanlisavsky-now widely known as the Method-began a revolution on the screen and made her an industry darling. Although popular with audiences and widely lauded for her versatile, naturalistic style, MacMahon's despair at the lack of challenging roles and fallout from her political activism would soon dim her star in the most tragic of ways. Blacklisted during the Communist Red Scare of the 1950's she became the subject of covert FBI surveillance and was denied work for many years.